Cā panʻʺ ʼalaṅkā kabyā myāʺ (Panʻʺ Myuiʺ Tacʻ rā Cā pe, 1994)
Laudatory poems for Ūʺ Paññāvaṃsa, b. 1929, Burmese Buddhist monk at Penang; contributed by Burmese poets on the occasion of the monk being conferred the title of Aggamahāpaṇḍita by the Burmese government.